Suicidal thoughts, problem gambling severity and utilisation of health care and social services: A population-based study in Finland - Latvala, Tiina; Heiskanen, Maria; Marionneau, Virve; Lind, Kalle; Grönroos, Tanja; Castrén, Sari (Elsevier BV, 2026)
Background
Persons harmed by problem gambling have an increased risk of suicide and suicidal thoughts. Social and health care services have an important role in recognising and supporting persons harmed by gambling problems and suicidal thoughts.
Methods
We analyse population-based survey data from the Healthy Finland survey of permanent Finnish residents aged 20 years or older (n = 28,154). We study associations between gambling and suicidal thoughts, and use of health care and social services among individuals engaged in gambling and experienced suicidal thoughts in the past year. The analysis uses χ2 tests and logistic regression models.
Results
Of persons harmed by problem gambling (PGSI score ≥ 8) 31 % had suicidal thoughts. Among persons harmed by problem gambling and having suicidal thoughts, utilization of health care and social services was more common compared to non-gamblers with suicidal thoughts. Individuals who engaged in gambling and experienced suicidal thoughts in the past year but had not utilized health care services were more often young, male, and excessive alcohol users. On the contrary, those who had used social services, engaged in gambling and had suicidal thoughts were experiencing more often long-term illnesses and severe psychological distress.
Conclusions
Suicidal thoughts are prevalent among persons harmed by problem gambling. Social and health service systems need to better recognise the association between gambling and co-occurrent suicidal thoughts. In addition, services need to be developed to offer effective treatment and support with high levels of integration.